Vegetative rescue and propagation of Australian red cedar by cuttings - Pereira, Mariane de Oliveira; Wendling, Ivar; Nogueira, Antônio Carlos; Kalil Filho, Antonio Nascim; Navroski, Marcio Carlos (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate vegetative rescue methods for the production of cuttings (clearcutting, full annealing, and half‑annealing) of red cedar (Toona ciliata var. australis) mature trees. The number of produced shoots was evaluated at 60, 120 and 180 days, as well as the correlation between stem mean diameter at breast height (DBH) and the number of sprouts. From the resulting sprouts of each method, cuttings were produced and subjected to cutting and removal of leaflets, and then received the application of indolbutyric acid (IBA) (0 and 6,000 mg L‑1). Evaluations were made for the influence of the following factors on plant survival and rooting: rescue method, collection time, number of leaflets of cuttings, and matrix tree, in the presence and absence of IBA. There was no correlation between the DBH of trees and the number of produced shoots. Clearcutting at 120 days provided the highest increase of shoots (15.31). Cuttings obtained from half‑annealing had higher survival (57.8%) and rooting (55.5%) rates. Cuttings with two pairs of preserved leaflets and treated with 6,000 mg L‑1 IBA showed higher rates of survival (65.5%) and rooting (56.7%). There was wide variation in survival and rooting capacity among matrix trees. The vegetative rescue and propagation by cuttings have potential for clonal multiplication of Australian red cedar mature trees.
Keywords: Toona ciliata; rooting; assexual propagation; vegetative propagation; clonal forestry